Increasing Knowledge About the Relationship Between Screen Time and Speech Delay Occurrence at Haji Regional Hospital, East Java Province - Salsabila Indrasari; Dyah Retno Wulan; Farika Zayrina; Adisti Amalia Suwarno; Iasha Maylaidine Devi Sillalahi (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2026)
Background: Language development is a crucial aspect of a child's growth and development, influenced by various factors, including environmental stimulation. One emerging factor receiving significant attention is excessive digital media use, or screen time. Uncontrolled screen time can lead to developmental problems, including speech delays in children. Most parents remain unaware of appropriate screen time limits and their impact on children's language development, highlighting the need for effective educational interventions. Objective: This study aimed to increase the knowledge of family members of pediatric patients at Haji General Hospital, East Java Province, regarding the relationship between screen time and speech delays. Methods: The method used was descriptive-analytical, with educational delivery using PowerPoint presentations and leaflets, as well as formative evaluation activities in the form of pretests and posttests. These were then analyzed using a paired-group pretest-posttest design using SPSS. Results: The paired t-test analysis comparing pretest and posttest scores showed a statistically significant difference (p = 0.045), indicating an increase in family knowledge regarding the relationship between screen time and speech delays.